Current epidemiology of resistance among Gram-negative bacilli in paediatric patients in Turkey. (December 2017) - Aykac, Kubra; Ozsurekci, Yasemin; Tanır Basaranoglu, Sevgen; Akin, Mustafa Senol; Cengiz, Ali Bulent; Bicakcigil, Asiye; Sancak, Banu; Kara, Ates; Ceyhan, Mehmet
Highlights: Resistance of Gram-negative bacteria to amikacin, ciprofloxacin, carbapenems and colistin increased from 2014. Klebsiella spp. was the most common cause of Gram-negative nosocomial infection in children, with high resistance rates. Acinetobacter spp. was associated with higher infection-related and overall mortality rates. Abstract: Objectives: The increasing incidence of infections caused by drug-resistant Gram-negative organisms has led to a re-emergence worldwide. This study attempted to investigate the changes in resistance of Gram-negative bacteria to different classes of antibiotics and the treatment options for invasive infections. Methods: A retrospective study was performed between January 2012 and January 2017 in a Turkish tertiary care university hospital. A total of 302 patients with Gram-negative bacteraemia ( n  = 274; 90.7%) or meningitis ( n  = 28; 9.3%) were identified and their demographic, clinical and microbiological features were evaluated. Results: A total of 302 patients with Gram-negative bacterial infection (bacteraemia or meningitis) were investigated. Klebsiella spp. was the most frequent causative agent ( n  = 119; 39.4%), followed by Escherichia coli ( n  = 67; 22.2%), Acinetobacter spp. ( n  = 42; 13.9%), Pseudomonas spp. ( n  = 41; 13.6%) and Enterobacter spp. ( n  = 33; 10.9%). In total, 115 isolates (38.1%) were multidrug-resistant (MDR), 63 (20.9%) were extensively drug-resistant (XDR) and 6 (2.0%) were pandrug-resistant (PDR). Over the years, peak antibiotic resistance occurred in 2013, with an increase in the following years. Conclusions: These data indicate that the resistance pattern of Gram-negative bacteria may change over the years in hospital settings. Therefore, active surveillance of the resistance patterns of micro-organisms is necessary for better management of infections caused by highly resistant bacteria.